Specialized software for estimating transmission line and substation lightning performance. Issue 4 (October 2015) - Banjanin, Mladen; Savić, Milan
This paper describes specialized software developed to estimate substation and transmission line performance during lightning events. Comparison with similar software packages is also discussed and advantages are noticed. Additionally, this paper describes specific program features that could be applied in the education of students. Supporting computational exercises included in subject curriculum are given as well. The aim of every exercise is clearly defined and some of the estimated results are included. Introduction of presented software package in course curriculum allows teachers to present fundamental concepts and results. Such information attracts students' attention and makes the lessons more interesting. This leads to better understanding of the presented materials.